Virtual Reality in Festivals: A Systematic Literature Review and Implications for Consumer Research - Daisy Lee; Peggy M.L. Ng; Tai Ming Wut (Emerging Science Journal, 2022)
Technological advancements in virtual reality have influenced festivalgoers, performers, and festival organizers. Due to the COVID-19 pandemic, organizers of cultural and tourism festivals have sought to deliver festivals online using virtual reality to provide an immersive experience from home. However, despite growing interest in virtual reality for festivals, there is no current systematic review to synthesize knowledge from academic papers within the festival context. This paper aims to provide a structured understanding of extant virtual reality research regarding festivals by using a systematic literature review. After a comprehensive review of extant literature from major databases, 19 relevant articles were extracted and synthesized according to the types, venues, roles, and objectives of the virtual reality applications. This study is the first systematic literature review to examine the current landscape of consumer research on virtual reality in festivals. Our results show that the limited numbers of extant literature concerning virtual reality in festivals indicates that this is an important yet significantly under-researched topic for future research. Current literature on virtual reality in festival contexts also lacks an in-depth understanding of consumer engagement and experiences. This paper recommends incorporating the application of theory and robust consumer research methods into future virtual festival research. Doi: 10.28991/ESJ-2022-06-05-016 Full Text: PDF